Synthesis, characterization, anticancer activity, optical spectroscopic and docking studies of novel thiophene-2-carboxaldehyde derivatives - Shareef, Mohamed Ahadu; Musthafa, Mohamed; Velmurugan, Devadasan; Karthikeyan, Subramani; Ganesan, Singaravelu; Padusha, Syed Ali; Musthafa, Saiyad; Mohamed, Jamal (European Journal of Chemistry, 2016)
2-((4-Methylpiperazin-1-yl)(thiophen-2-yl)methyl)hydrazinecarboxamide (L1) and (2-(piperazin-1-yl(thiophen-2-yl)methyl)hydrazinecarboxamide (L2) from the family of thiophene-2-carboxaldehyde derivatives have been synthesized. These new compounds have good antibacterial as well as antifungal activity and also less toxic in nature. Exemplary binding characteristics of these novel compounds and pharmacokinetic mechanism were confirmed by optical spectroscopic, anticancer and docking studies. The binding of thiophene-2-carboxaldehyde derivatives to carrier protein, Human Serum Albumin (HSA) has been investigated by studying its quenching mechanism, binding kinetics and the molecular distance (r) between donor (HSA) and acceptor (thiophene-2-carboxaldehyde derivatives) according to Forster’s theory of non-radiative energy transfer (FRET). The micro environment of HSA has also been studied by using synchronous fluorescence spectroscopy technique and the molecular docking technique has been used to explore the hydrogen bonding, hydrophobic interaction between the human serum albumin with L1 and L2 compound.